Testing for Information Asymmetries in Real Estate Markets - Kurlat, Pablo; Stroebel, Johannes (Review of Financial Studies, 2015)
In housing markets, neighborhood characteristics are a key source of information heterogeneity: sellers are usually better informed about neighborhood values than buyers are, but some sellers and buyers are better informed than their peers are. Consistent with predictions from a new framework for analyzing such markets with heterogeneous assets and differentially informed agents, we find that changes in the composition of sellers toward more informed sellers and sellers with a larger supply elasticity predict subsequent house price declines. This effect is larger for houses with more price exposure to neighborhood characteristics, and smaller for houses bought by buyers that are more informed.